Differential Taxation and Corporate Futures-Hedging - Jack E. Wahl; Udo Broll (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
Using a two-moment decision model this paper analyzes corporate hedging behavior in the presence of unified and differential income taxation. We start with the well-known result that risk-taking may increase when income tax rates increase and, therefore, the incentive for hedging reduces. We demonstrate that pure hedging is differently affected by taxation than speculative hedging is. Analysing tax-sensitivity of the corporate hedge shows that a higher risk in the first place may reduce the tax-induced incentive to revise a futures position.
Keywords: F31; F21; H20; 330; taxation; hedging; mean-variance model; unified and differential taxation; Roy preference function; Risikomanagement; Hedging; Einkommensteuer; Einkommensteuertarif; Steuerwirkung; Risikopräferenz; Theorie